2014
DOI: 10.1007/s11250-014-0722-2
|View full text |Cite
|
Sign up to set email alerts
|

Grouping previously unknown bucks is a stressor with negative effects on reproduction

Abstract: Grouping previously unknown animals produces social stress, which might have negative effects on reproduction. The aims of the experiment were to determine if grouping unknown bucks (1) triggers a stress response and produces changes in body weight; (2) affects scrotal circumference, testosterone concentration, and semen quality; and (3) has differential effects between resident and introduced bucks. One group of nine Saanen bucks was transported and introduced (introduced bucks, group IG) to a group of eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…In the same sense, in goats, it has been shown that mixing bucks provokes a marked increase in the number of aggressive (Sánchez-Dávila et al, 2018) and sexual interactions (Ungerfeld et al, 2013) in the group. This is also accompanied by increases in cortisol concentration (Giriboni et al, 2015;Sánchez-Dávila et al, 2018), and negatively affects testosterone production, testicular size, and seminal quality for at least 20 days (Giriboni et al, 2015). Although in this survey the seminal quality was not evaluated, some breeders mentioned the negative effect of mounting between bulls on it, as well as on libido, affecting directly even in marketing (return of bulls).…”
Section: Discussionmentioning
confidence: 90%
“…In the same sense, in goats, it has been shown that mixing bucks provokes a marked increase in the number of aggressive (Sánchez-Dávila et al, 2018) and sexual interactions (Ungerfeld et al, 2013) in the group. This is also accompanied by increases in cortisol concentration (Giriboni et al, 2015;Sánchez-Dávila et al, 2018), and negatively affects testosterone production, testicular size, and seminal quality for at least 20 days (Giriboni et al, 2015). Although in this survey the seminal quality was not evaluated, some breeders mentioned the negative effect of mounting between bulls on it, as well as on libido, affecting directly even in marketing (return of bulls).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have evaluated the social hierarchy in rams raised in pairs, identifying that the dominant males exhibit a greater sexual precocity and a greater reproductive capacity compared to the subordinate males. A negative influence on testosterone production has also been reported, due to the stress of the grouping of bucks [34][35][36].…”
Section: Male Social Hierarchy and Its Impact On Reproductionmentioning
confidence: 99%
“…Among the responses at the physiological level present in male goats in stressful situations is the secretion of glucocorticoids (GC), which exert a negative feedback effect on the hypothalamic-pituitary-gonadal axis, reducing the synthesis of GnRH and together thereby inhibiting the synthesis of gonadotropins and sex steroid hormones [34,39]. This endocrine mechanism aims to stimulate the body to respond to stressors, such as loss of appetite, suppression of the immune system, energy mobilization, vasoconstriction, and loss of erection and receptive sexual behaviors [42].…”
Section: Cortisol and Stress Physiology In Bucksmentioning
confidence: 99%
“…En muchas situaciones vinculadas a la producción animal, las respuestas indicadoras de estrés no logran modificar la situación que las generó (25) . Esto sucede, por ejemplo, luego del destete, en que los animales no logran juntarse nuevamente (26) , durante el transporte en que el animal no puede evitar su traslado, o durante el reagrupamiento social (27) , en que el animal debe adaptarse a convivir con nuevos individuos previamente desconocidos. En estos casos, las respuestas son costosas para el animal, pero no se modifica la situación, por lo que el resultado final es deletéreo en lugar de ventajoso.…”
Section: Chronic Responseunclassified
“…In many situations related to animal production, the response is not enough to modify the situation (25) . This happens, for example, after weaning, in which animals fail to reunite again (26) , during the transport in which the animal cannot avoid its transfer, or after social grouping, as animals must adapt to live with new previously unknown individuals (27) . In these cases, the responses are expensive for the animal, and does not end changing the situation, so the result is deleterious rather than advantageous.…”
Section: Progesterona Y Respuesta De Estrés: Mecanismos De Acciónmentioning
confidence: 99%